2015
DOI: 10.3390/f6051422
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Forest Lightning Fire Occurrence in the Daxinganling Mountains of Northeastern China with MAXENT

Abstract: Forest lightning fire is a recurrent and serious problem in the Daxinganling Mountains of northeastern China. Information on the spatial distribution of fire danger is needed to improve local fire prevention actions. The Maxent (Maximun Entropy Models), which is prevalent in modeling habitat distribution, was used to predict the possibility of lightning fire occurrence in a 1 × 1 km grid based on history fire data and environment variables in Daxinganling Mountains during the period 2005-2010.We used a jack-kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 34 publications
1
39
0
1
Order By: Relevance
“…As shown in Figure 4, most of the lightning-caused fires (i.e., >98%) in all of the natural subregions happened during the growing season (i.e., from snow disappearance date in spring to the start of snowfall in autumn). The reason for such a trend might be related to the extensive availability of fuels, and the occurrence of the lightning storms as a fire ignition source in the region [7,39,40]. Even though we observed that a significant proportion of the fires took place during the growing season, we also observed a small amount of fires (i.e., <2%) before the growing season started, which could be related to dead branches, peat, or duff beneath the trees that remained from the previous year, and were initially ignited by lightning strikes in late winter [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4, most of the lightning-caused fires (i.e., >98%) in all of the natural subregions happened during the growing season (i.e., from snow disappearance date in spring to the start of snowfall in autumn). The reason for such a trend might be related to the extensive availability of fuels, and the occurrence of the lightning storms as a fire ignition source in the region [7,39,40]. Even though we observed that a significant proportion of the fires took place during the growing season, we also observed a small amount of fires (i.e., <2%) before the growing season started, which could be related to dead branches, peat, or duff beneath the trees that remained from the previous year, and were initially ignited by lightning strikes in late winter [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…However, validation showed a relatively weak relationship (R 2 = 0.44) between the modeled and observed values. In another study conducted over the Daxinganling Mountains of Northeastern China, Chen et al [7] predicted lightning-caused fire occurrences at 1-km spatial resolution during the 2005-2010 period. In this case, they used several datasets, including: (i) historical fire data, i.e., number of lightning strikes and lightning current intensity; (ii) meteorological data, i.e., rainfall, temperature, relative humidity, and wind speed; (iii) topographical elements, i.e., elevation, slope, and aspect; and (iv) fuel type, i.e., larch forest, Scots pine forests, mixed forest with larch, birch and oak trees, mixed forest with Scots pine, birch and oak trees, and grass.…”
Section: Introductionmentioning
confidence: 99%
“…In China, research has focused on occurrences of lightning‐ignited forest fires [ Chen et al ., ], the relationships between fire occurrence and climate drivers [ Liu et al ., ; Ullanm et al ., ], and the impacts of fires on forest ecosystems [ Lü et al ., ; X. Li et al ., ]. These studies have improved understanding of fire characteristics and their effects on forest ecosystem functions at the stand or local scale.…”
Section: Introductionmentioning
confidence: 98%
“…In China, research has focused on occurrences of lightning-ignited forest fires [Chen et al, 2015], the relationships between fire occurrence and climate drivers [Liu et al, 2012;Ullanm et al, 2013], and the impacts of fires on forest ecosystems [Lü et al, 2006;X. Li et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Meteorological features like average precipitation, temperature, humidity and wind speed have been used to understand forest re characteristics. In other studies lightening has been focused to predict forest re (Chen et al 2015).…”
Section: Introductionmentioning
confidence: 99%